(untitled) (Journal of Philosophy, Culture and Political Science, 2025)
The article deals with the role of electronic petitions as a means of political communication, with a particular focus on the experiences of the United Kingdom and the evaluation of its applicability to Kazakhstan. The analysis examines the challenges to the e-petitioning practice, comparing the institutionalized frameworks and assessing its effectiveness in fostering political participation. The study also questions key indicators of success or failure of e-petitions. The case studies cover the differences in the legal and institutional framework for e-petitions in the UK and Kazakhstan, as well as the impact of external actors. The study also evaluates how institutional setup, political culture, including, political situation, and political polarization, in each country, affects the responsiveness of governments to petitions. The authors point at the limitations of e-petitions as a tool for democratic engagement and at the significant bureaucratic and institutional constraints in both cases, including the lack of mechanisms to ensure a meaningful response, as well as the frequent disregard of petitions, when they challenge established policies or political agendas of governments. Keywords: E-petitions, political communication, digital democracy, political participation, citizen engagement, digital activism.